The assessment of essential oil potential from waste logging of different eucalyptus clones in PT Toba Pulp Lestari Tbk’s industrial plantation forests, Indonesia - Purwoko, Agus; Muhdi; Sari, Rita Kartika; Azhar, Irawati; Sianturi, Yulyanti Ria Utami; Sembiring, Haganta (Plant Science Today, 2024)
PT. Toba Pulp Lestari Tbk's Industrial Plantation Forest is the largest forest company in North Sumatra Province, with a total area of 188055 ha. Eucalyptus leaves in this company have not been optimally utilized and processed, commonly left as waste. This study aims to calculate the potential of leaves and the potential production of essential oils from eucalyptus leaves which are waste from logging. The method used to calculate the potential of eucalyptus leaves from logging waste is to measure the weight of the leaves from the sample tree. The yield of essential oils produced from eucalyptus leaves is obtained through distillation techniques in the laboratory. The annual production potential of essential oils is calculated using annual logging area data for each clone. The study produced average data on eucalyptus leaf potential from logging waste for each clone and the entire logging area per year. Distillation was performed on all clones to produce eucalyptus oil's average yield and density. Conversion of yield with leaf potential and area of felling results in the amount of oil produced from felled logging waste leaf per year. The potential for eucalyptus production is very significant and related to efforts to increase the economy of non-timber forest products.